Pengaruh Olahraga Tradisional Terhadap Peningkatan Kebugaran Jasmani Pada Siswa UPTD SD Negeri 51 Barru - Iyan; Usman (STKIP Andi Matappa Pangkep, 2024)
Physical fitness is the body's ability to carry out physical activities without experiencing excessive fatigue. This research aims to find out whether there is an influence of traditional sports games on improving students' physical fitness. This research uses a one-group pretest-posttest design. The research population consisted of all UPTD students at SD Negeri 51 Barru, totaling 72 students, with a sample taken of 20 class V students. The instrument used in data collection was a test for children. To test the hypothesis, tests, and data analysis were used using the t-test, normality test, and homogeneity test. Based on the t-test results, the calculated t-value was 3.533, greater than the t-table of 1.710 (3.533 > 1.710). This shows a significant difference between the data before and after treatment. The average pretest score was 11.20, while the average posttest was 13.95, which means there was an increase in physical fitness of 2.20 or 15.23%. In conclusion, there was a significant increase in physical fitness in class V UPTD students at SD Negeri 51 Barru after taking part in traditional sports lessons.